2012
DOI: 10.4995/eurocall.2012.11379
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Digital Storytelling for ESP in a Technical English Course for Aerospace Engineers

Abstract: <p>Digital Storytelling is a powerful pedagogical tool for both students and educators, which started to be used for teaching and learning purposes a few years ago, becoming more and more popular over time. The use of digital storytelling in non-specific language learning contexts has been widely explored, as shown in the literature. However, its use in technical-scientific contexts of English for Specific Purposes (ESP) has not been so widely studied. This paper explores a project of digital storytellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 5 publications
2
8
0
1
Order By: Relevance
“…They appeared to care more about putting into action newly-acquired generic and technological knowledge, exploring task management skills, and critically evaluating task decisions and conditions during teamwork. Congruent with their predecessors' self-reports, the participants corroborated the following benefits of digital storytelling in collaborative groups for: i. improved language skills (Kent, 2011;Kim, 2018;Ming et al, 2014;Oskoz & Elola, 2014;Ramirez, 2013;Reyes-Torres et al, 2012;Soler-Pardo, 2014) Sepp, 2014;Genereux & Thompson, 2008;Maddin, 2012;Sevilla-Pavon et al, 2012;Yang & Wu, 2012).…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…They appeared to care more about putting into action newly-acquired generic and technological knowledge, exploring task management skills, and critically evaluating task decisions and conditions during teamwork. Congruent with their predecessors' self-reports, the participants corroborated the following benefits of digital storytelling in collaborative groups for: i. improved language skills (Kent, 2011;Kim, 2018;Ming et al, 2014;Oskoz & Elola, 2014;Ramirez, 2013;Reyes-Torres et al, 2012;Soler-Pardo, 2014) Sepp, 2014;Genereux & Thompson, 2008;Maddin, 2012;Sevilla-Pavon et al, 2012;Yang & Wu, 2012).…”
Section: Discussionmentioning
confidence: 54%
“…They apparently liked to work on different parts (sequentially) at different times (asynchronously) in different locations (distributedly), avoided face-to-face conversations outside the classroom, and diminished their chances of consensus and control over their CDS projects; therefore, as Lowry et al (2004) pointed out, poor communication and weak relationships might have led to their poorer performance. Several previous studies on CDS activities had also documented positive overall results, attempts for complex structures, relatively fewer grammar errors, and skilful use of technology, mainly through teacher-led global evaluations (Alcantud-Diaz, 2016;Ramirez, 2013;Reyes-Torres et al, 2012;Sevilla-Pavon et al, 2012;Soler-Pardo, 2014), but Kim's (2018) CAF analysis alone showed that despite no significant development in fluency and complexity, multiple practices of peer-editing increased L2 writing accuracy, when partners worked well together towards the same end.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations